Clinical Outcome of Sacroiliac Rod Fixation for Fragility Fracture of the Pelvis Rommens and Hoffman Classification Type IVb: Case Series. (16th November 2022) - Gamada, Hisanori; Yanagisawa, Yohei; Teruya, Shotaro; Eda, Yusuke; Nakagawa, Tsukasa; Yamazaki, Masashi
Introduction: Fragility fracture of the pelvis (FFP), generally involving Rommens and Hoffman classification type IVb (H-shaped) requires spinopelvic fixation (SPF). We report the clinical outcome of sacroiliac rod fixation (SIRF) for FFP type IVb in a case series. Materials and Methods: In this retrospective observational study, six patients (mean age, 80.3 years; range, 74-85 years) with FFP type IVb who underwent SIRF since October 2019 and could be followed up for ≥1 year postoperatively were included. All patients were injured in low-energy falls, a patient had a femoral neck fracture, and other had a humeral neck fracture and distal radius fracture. Results: The mean (range) operative time was 135 (98-200) min, and mean blood loss was 103 (80-130) g. All patients achieved bone union in an average of 4.3 months. No implant failure or surgical site infection requiring reoperation occurred. No patient complained of iliac screw irritation or requested removal. One patient developed a T12 vertebral fracture at 3 weeks postoperatively. The mean final follow-up period was 17.8 months (13-22 months) and mean final modified Majeed Score (maximum 76 points as the items "work" and "sexual intercourse" were omitted for this study) was 71.7 (56-76). Conclusions: SIRF is a less invasive surgical technique than SPF that uses only an S1 pedicle screw and iliac screw. SIRF using the "within ring" concept showed good clinical outcome in FFP type IVb.